Students' Beliefs about Willingness to Access Complementary and Alternative Therapies (CAT) Training for Future Integration into Psychology Practice. (24th June 2012) - Wilson, Lee-Ann M.; Hamilton, Kyra; White, Katherine M.
Abstract : It is suggested that all psychologists gain basic training in the types of complementary and alternative therapies (CAT) their clients may be using. As psychology students are the next cohort of health professionals who will inform future initiatives in the field, it is important to understand the factors which influence their decisions about CAT integration. Drawing on the theory of planned behavior, we investigated the beliefs that differentiate between psychology students who are high or low on willingness to access training in CAT for future practice use. Undergraduate psychology students (N = 106 ) completed a questionnaire assessing the likelihood of positive and negative consequences of accessing training and utilizing CAT within a psychological practice, important others' approval, and barriers preventing them from this integration behavior. Those students higher on willingness were more likely to endorse positive outcomes (e.g., offering a more holistic approach to therapy) of accessing CAT training for future practice use and to believe that important others (e.g., clients) would support this behavior. A regression analysis examining the relative importance of these belief sets broadly supported the belief-based analyses. These beliefs of student psychologists can inform educators and policy makers about CAT training and integration in psychology practice.